Refractive error and visual impairment in Ireland schoolchildren - Síofra Harrington; Jim Stack; Kathryn J. Saunders; Veronica O’Dwyer (2018)
Aim To report refractive error prevalence and visual impairment in Republic of Ireland (henceforth 'Ireland') schoolchildren. Methods The Ireland Eye Study examined 1626 participants (881 boys, 745 girls) in two age groups, 6–7 years (728) and 12–13 years (898), in Ireland between June 2016 and January 2018. Participating schools were selected by stratified random sampling, representing a mix of school type (primary/postprimary), location (urban/rural) and socioeconomic status (disadvantaged/advantaged). Examination included monocular logarithm of the minimum angle of resolution (logMAR) presenting visual acuity (with spectacles if worn) and cycloplegic autorefraction (1% Cyclopentolate Hydrochloride). Parents completed a questionnaire to ascertain participants’ lifestyle. Results The prevalence of myopia (spherical equivalent refraction (SER): ≤−0.50 D), hyperopia (SER: ≥+2.00 D) and astigmatism (≤−1.00 DC) among participants aged 6–7 years old was 3.3%, 25% and 19.2%, respectively, and among participants aged 12–13 years old was 19.9%, 8.9% and 15.9%, respectively. Astigmatic axes were predominately with-the-rule. The prevalence of ‘better eye’ presenting visual impairment (≥0.3 logMAR, with spectacles, if worn) was 3.7% among younger and 3.4% among older participants. Participants in minority groups (Traveller and non-white) were significantly more likely to present with presenting visual impairment in the ‘better eye’. Conclusions The Ireland Eye Study is the first population-based study to report on refractive error prevalence and visual impairment in Ireland. Myopia prevalence is similar to comparable studies of white European children, but the levels of presenting visual impairment are markedly higher than those reported for children living in Northern Ireland, suggesting barriers exist in accessing eye care.